ANALYSIS OF DRY BULK CARGO LOADING AND UNLOADING PERFORMANCE AT TANJUNG TEMBAGA PORT (CASE STUDY : PT DELTA ARTHA BAHARI NUSANTARA) - Ilma Nur Fadhila Aghnia; Dian Junita Arisusanty; Anak Agung Sri Wahyuni; Jose Beno (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
In recent years, loading and unloading activities at ports have shown a significant increase in line with the growth in global and regional trade volumes. However, the surge in loading and unloading activities poses serious challenges, such as limited infrastructure, stacking capacity, operational efficiency, the need for more and more qualified human resources, and compliance with increasingly stringent regulations, in addition to environmental impacts and safety aspects that need to be considered. The purpose of this study is to identify and evaluate the main obstacles that arise due to the increase in dry bulk loading and unloading activities at PT DABN Port, as well as strategic solutions to overcome these challenges in order to ensure the smooth operation and sustainability of the port environment. The research method used is a quantitative approach by conducting a survey using key performance indicators such as loading and unloading time, labor productivity, equipment utilization, and damage rate. Primary data used comes from questionnaire answers with a total of 30 respondents, while secondary data is obtained from company reports and official port documents. This research uses descriptive analysis using validity and reliability tests using a used trial. The results showed that the performance of dry bulk loading and unloading at PT DABN Port was in the good category, but from these indicators there were still obstacles for service users. These obstacles will be an evaluation for PT DABN to improve loading and unloading performance from the aspects of equipment utility, loading and unloading time, labor productivity and the level of damage to goods and make improvements as a determinant of the success of dry bulk loading and unloading so as to increase loading and unloading efficiency.